Bone marrow fat, visceral fat, and body conditions as parameters of possible neglect in dogs with leishmaniasis - Morais, Hugo Ribeiro [UNESP]; Março, Karen Santos [UNESP]; Bregano, Lívia Castanhas [UNESP]; Grassi, Thiago Luís Magnani; Seraguci, Tulio Faria [UNESP]; Jussiani, Giulia [UNESP]; de Melo, Guilherme Dias; Cipriano, Rafael; Ponsano, Elisa Helena Giglio [UNESP]; Machado, Gisele Fabrino [UNESP] (Elsevier, 2022)
This study aimed to verify the body condition parameters that can be used to characterise possible cases of neglect in dogs with visceral leishmaniasis. Fifty dogs were used in the study. The control group contained 11 dogs. Of the 39 infected dogs, 25 and 14 were included in the multisymptomatic and oligo/asymptomatic groups, respectively. The parameters evaluated included body score, body mass index, bone marrow fat percentage (Soxhlet method), bone marrow supernatant fat content (mm in a 15-ml tube), and visceral fat content. We observed that most euthanised dogs with canine leishmaniasis were multisymptomatic, implying that they were unwell and had a low body condition score. This condition is associated with low bone marrow fat content and maintenance of visceral fat reserves. Therefore, the assessment of body score and bone marrow fat content associated with visceral fat content can be used as evidence of neglect in dogs with visceral leishmaniasis.
Keywords: Abuse; Cachexia; Leishmania spp.